Nawakōwāt (laksūt naktham chan trī) - Wachirayānawarōrot, Prince, son of Mongkut, King of Siam, Supreme Patriarch, 1860-1921.; Phimon Kō̜pngœ̄nthō̜ng, 1919-1979. ([Krung Thēp Mahā Nakhō̜n : Khrō̜pkhrūa Phan Tamrūat Thō Phimon Kō̜pngœ̄nthō̜ng : Mahāmakut Rātchawitthayālai], 1979)
Textbook for novice monastics in two parts, this part dealing with discipline; includes text of Winayabanyat, cremation volume for Phan Tamrūat Thō Phimon Kō̜pngœ̄nthō̜ng, Thai policeman; includes biography.
In Thai.
Keywords: Phimon Kō̜pngœ̄nthō̜ng, -- 1919-1979 -- Death and burial; Tipiṭaka. -- Criticism, interpretation, etc; Buddhist monasticism and religious orders -- Rules